2013
DOI: 10.1096/fj.13-235614
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D1 primes the resolution process initiated by calorie restriction in obesity‐induced steatohepatitis

Abstract: Insulin resistance and nonalcoholic steatohepatitis (NASH), characterized by hepatic steatosis combined with inflammation, are major sequelae of obesity. Currently, lifestyle modification (i.e., weight loss) is the first-line therapy for NASH. However, weight loss resolves steatosis but not inflammation. In this study, we tested the ability of resolvin D1 (RvD1), an anti-inflammatory and proresolving molecule, to promote the resolution initiated by calorie restriction in obese mice with NASH. Calorie restricti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 42 publications
9
69
0
Order By: Relevance
“…A recent study showed that inhibition of either the BLT 1 receptor or the cysteinyl leukotriene 1 receptor decreases expression of both miRNAs in macrophages. Additionally, miR-125b-5p expression was decreased in BLT 1 2/2 mice compared with wild-type mice (12) and is upregulated by resolvin D1 (45). These observations and our data suggest a possible negative feedback regulation of 5-LO via the 5-LO products by induction of these two miRNAs.…”
Section: Discussionsupporting
confidence: 73%
“…A recent study showed that inhibition of either the BLT 1 receptor or the cysteinyl leukotriene 1 receptor decreases expression of both miRNAs in macrophages. Additionally, miR-125b-5p expression was decreased in BLT 1 2/2 mice compared with wild-type mice (12) and is upregulated by resolvin D1 (45). These observations and our data suggest a possible negative feedback regulation of 5-LO via the 5-LO products by induction of these two miRNAs.…”
Section: Discussionsupporting
confidence: 73%
“…The results of the present investigation indicate that inhibition of sEH when there is an increased content of omega-3 PUFA exerts a more favorable role in counteracting the metabolic disorders associated with obesity. In addition, our findings expand focus to include EpFA to the protective actions described for those lipid mediators derived from omega-3s through lipoxygenase-and cycloxygenase-initiated pathways (i.e., resolvins, protectins, and maresins) (16,17).…”
Section: Significancementioning
confidence: 82%
“…Here, we explored the metabolic effects of a sEH inhibitor (t-TUCB) in fat-1 mice with transgenic expression of an omega-3 desaturase capable of enriching tissues with endogenous omega-3 PUFA. These mice exhibited increased CYP1A1, CYP2E1, and CYP2U1 expression and abundant levels of the omega-3-derived epoxides 17,18-epoxyeicosatetraenoic acid (17, in insulinsensitive tissues, especially liver, as determined by LC-ESI-MS/MS. In obese fat-1 mice, t-TUCB raised hepatic 17,18-EEQ and 19,20-EDP levels and reinforced the omega-3-dependent reduction observed in tissue inflammation and lipid peroxidation.…”
mentioning
confidence: 97%
“…In several studies, RvD1 has been reported to inhibit COX-2 generation to protect tissues from inflammatory injury in many diseases, such as lung injury (32) and steatohepatitis (42). Unlike COX-2 genetic deletion or pharmacological inhibition by nonsteroidal anti-inflammatory drugs, both of which result in exacerbation of inflammatory injury and impairment of recovery, RvD1 upregulated proresolving COX-2 expression in the later phase of inflammation to prompt resolution.…”
Section: Figurementioning
confidence: 99%